Some Biological Aspects of Spotted Barb Barbodes binotatus (Valenciennes, 1842) in Tamblingan Lake - Ni Made Sita Aditya Putri; Nyoman Dati Pertami; I Nyoman Yoga Parawangsa (Jurnal Perikanan Universitas Gadjah Mada, 2022)
The biological aspects of the spotted barb, Barbodes binotatus (Valenciennes, 1842) in Tamblingan Lake were not published yet. This study aims to determine the biological aspects of spotted barb in Tamblingan Lake. Fish samples were captured using gill nets with various mesh sizes at five fixed stations monthly from January to December 2019. A total of 357 individuals of the spotted barb was collected, with the total length of the specimens ranging from 3.9 to 15.6 cm, and total weight varied between 0.93 and 60.30 g. The length-weight relationship for males and females were expressed as W = 0.0375L2.83 and W = 0.0272L3.02, respectively. The growth pattern for males and females was allometric negative and isometric, subsequently. The male-female sex ratio was 1.10:1, and the condition factor for males and females were 0.75-1.42 and 0.40-1.49, respectively. We observed male fish with gonad maturity stage I to IV. In contrast, female fish have gonad maturity stage II to V. The highest gonadosomatic index of male and female fish was found in September, indicating a peak of the spawning time. Fecundity ranged from 57-23897 eggs, with an average of 5901 eggs.